Diet, body condition and seasonal stress in American Black Duck Anas rubripes and Mallard A. platyrhynchos on Long Island, New York, during winter - Flores, Aidan J.; Schummer, Michael L. (Wildfowl, 2024)
Winter habitat for the American Black Duck Anas rubripes (hereon Black Duck) has decreased on the Atlantic coast of North America because of urbanisation and other factors. Human development makes restoration of coastal wetlands for wildlife difficult, but agriculture could increasingly provide food for Black Duck during winter. Diet, body condition and stress indices of Black Duck and Mallard A. platyrhynchos were compared between coastal wetlands and sites with Corn Zea mays fields on Long Island, New York, used by the birds from late-January to late-March. Black Duck and Mallard were captured at Corn sites, whilst only Black Duck were collected in coastal wetlands. Mallard were not available in coastal wetlands for collection during the study. Stable isotope analysis indicated that the Black Duck ate more animal matter (measured by a blood δ15N index) at coastal than Corn sites, whereas Mallard and Black Duck at Corn sites had similar animal diets, although Mallard ate more Corn (determined by blood δ13C levels) than Black Duck. Body mass decreased during the winter for Black Duck at both coastal and Corn sites but increased in Mallard at Corn sites. Stress indices, measured by packed red blood cell volume and heterophil/lymphocyte ratios, suggested less stress for Black Duck when using Corn than when at the coastal sites. Results suggest an endogenous mechanism for weight loss in the Black Duck during winter which differs from Mallards in our study area, although given that Black Duck generally appear to eat less Corn other factors not considered here may also contribute to the weight loss patterns. Overall, Black Ducks appeared to benefit less than Mallards from the availability of Corn. Where feasible, continued protection and restoration to increase quantity and quality of coastal wetlands should be the focus on Long Island and elsewhere where Black Duck and Mallard are sympatric.